If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(8 + -9x) + 1 = 0 (8 * 9 + -9x * 9) + 1 = 0 (72 + -81x) + 1 = 0 Reorder the terms: 72 + 1 + -81x = 0 Combine like terms: 72 + 1 = 73 73 + -81x = 0 Solving 73 + -81x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-73' to each side of the equation. 73 + -73 + -81x = 0 + -73 Combine like terms: 73 + -73 = 0 0 + -81x = 0 + -73 -81x = 0 + -73 Combine like terms: 0 + -73 = -73 -81x = -73 Divide each side by '-81'. x = 0.9012345679 Simplifying x = 0.9012345679
| 9(7m-9)-2= | | 6r-1+62=11 | | (4a^2/5b^4)^-2 | | -6w-13=5(w-7) | | 9+5(5-9r)= | | y^2-28y-132=0 | | x+1.1x+1.1(1.1x)+1.1(1.1(1.1x))+1.1(1.1(1.1(1.1x)))=1350 | | r^3+8r^2+16r= | | 5x=-3-2 | | -8(x+2)-9= | | r^2-18r=-56 | | 2v+2=-6 | | 3r^2/9r^3 | | -4n-4(10-9n)= | | x=3x+a-180 | | 25(x)-20= | | -7y=da | | -8p-5(5-8p)= | | 2(x-3)=6+2x | | 18-3x=-28 | | (x*0.15)+x=11.5 | | -9k-10(5k-8)= | | 16-2x+7=3x-4 | | x^2+ix+10=6x | | 1x+41=6 | | 10x^2-35=-65x | | 2-7(1-4x)= | | log(x)+log(7)=log(37) | | t-4a=9 | | 18-3=-12 | | 7+9x=3-5x | | x/8=-2/9 |